A Series of Publications in Japanese Studies: History, Politics, Foreign Policy, International Relations, Russia-Japan Relations and Japanese Studies in Russia - Anna A. Kireeva (Сравнительная политика, 2016)
A Series of Publications in Japanese Studies: History, Politics, Foreign Policy, International Relations, Russia-Japan Relations and Japanese Studies in Russia.